Los orientadores laborales. Trabajo cotidiano y efectos sobre sus públicos - MARTÍNEZ LÓPEZ , Antonio (Cuadernos de Relaciones Laborales, 2010)
In the social and labour context of last decades, marked by the growth of the school tidegrees and a parallel contraction of the working places, we can see to appear the active policies of employment that try to intervene in the law of supply and demand on the market. These policies trying to help individually the unemployed people in his labour insertion, and also to reducing the rates of unemployment. These policies deserve all the interest, for being the priority approach of the European Union as in relation to the employment and social intervention at present. In this text, we depart from a doctoral study in which a fundamentally qualitative analysis has been carried out on the network of centres of orientation in a one local area: the city of Granada. We will offer here, a sociological explanation on the role of the constrictions, the limits and the effects that the task of the labour councelors faces with his users.